Theatre in the Digital World. The Experiment of Theater Treffen 2020 - Decheva, Violeta (Sledva : NBU Journal of Humanities and Arts, 2020)
An overview and analysis of Berliner Theater Treffen 2020. Existing already for 56 years, this major European theatre festival and the most representative one for the Germanspeaking world ventured on its first online edition. COVID-19 situation has not only activated the ongoing discussions on the influence of digital technologies on theatre, but has made it a most urgent topic. It has become central because of the isolation, the sudden flood of streamings of concerts, performances, films, etc. Two topics seem especially important in the festival context. First, how to make theatre in a digital format and what kind of theatre phenomena are produced in consequence of such experiments. Second, what are the possibilities when streaming theatre productions.